Enigma do tempo: o problema da objetividade na contraposição entre Heidegger e Cassirer - Mergulhão, Adriano Ricardo (Universidade Federal de São Carlos, 2018)
This thesis analyses the objectivy problem in both Heidegger and Cassirer works, using the time concept as connecting thread for the comprehension of the existente counterpoint between their theories. This sistematic aprouch makes a reconcilemente of their main thesis possible, because both of them proposes a rereading of the kantian transcendental philosophy, using diferente aproaching methods for a common problem. Thus, the objectivity problem will be discussed, starting from the symbolic-epistemological perspective of Cassirer and the phenomenological-hermeneutic position of Heidegger, according to the positive contrast established between them. We propose that, even having some divergences, both authors enphasize the time concept centrality, implied to the imagination function, exposede in the chapter of the kantian transcendental schematism, as a ground for compreension of the objectivy problem. Therefore, we maintain that there is an interdependence from the antagonism of their positions, because, both center their arguments on the relation between the productive imagination and the objectivity, thematic that propitiates a common ground for the opening of a proficient dialogue. Therefor, the objectivity problem, goal of continuous inquiry in the Heidegger´s proposals and Cassirer´s motions, it will be only properly clarified with the analysis of implications that the time concept acquires in each philosopher’s doctrines, allowing in this way the reciprocal discernment of this theoretical purposes, that overcomes an one-side and preconceived theoretical dichotomy.
The enigma of time: the problem of objectivity in the counterpartment between Heidegger and Cassirer
Keywords: Objetividade; Tempo; Fenomenologia; Neokantismo; Objectivity; Time; Phenomenology; Neo-Kantianism; Heidegger, Martin, 1889-1976; Cassirer, Ernst, 1874-1945; Kant, Immanuel, 1724-1804; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA; CIENCIAS HUMANAS::FILOSOFIA::LOGICA; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA